KINERJA PEGAWAINEGERI SIPIL (PNS) PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN KUTAI TIMUR - Joni Salasiah (ADMINISTRASI PUBLIK, 2017)
This research aims to know and define ecological performance of Government Employees in Dinas Pengendalian Penduduk dan Keluarga Berencana East Kutai District along with the factors that inhibit and support the performance of Government Employees.The results of research and interview of the performance of Dinas Pengendalian Penduduk dan Keluarga Berencana East Kutai district had been appropriate affirmed whether this can be seen from the Factors supporting the performance of Government Employees in Dinas Pengendalian Penduduk dan Keluarga Berencana East Kutai district which is a sufficient infrastructure & facility and support the fluency of carrying the tasks that are given to the employees. But there is still something must be repaired because of resistance factors the performance of government employees  in Dinas Pengendalian Penduduk dan Keluarga Berencana East Kutai district amongst other limited  Human Resources and employees undisciplined.